Peran Islam di Asia Tenggara - A’yuninah, Kholidah Qurrota (Maliki Interdisciplinary Journal, 2024)
Islam is a religion revealed by Prophet Muhammad. Islam came and developed widely in the Southeast Asian region. And Islam has a lot of processes in its spread, such as using trade routes, marriage routes, tasawuf routes, education channels, artistic lines and political routes, Islam is a religion that has good signs where these signals are contained in the Alqur’anul Karim so easily accepted by the people in the Southeast Asian region. For the whole influence of Islam in Southeast Asia has given birth to a struggle as well as articulation and assimilation with the culture in the region, and produce a new culture that is dynamic and unique. With this Islam was accepted peacefully, and the development of Islamic civilization occurred in various aspects. Therefore, Southeast Asia is a field of struggle, as well as acculturation and assimilation of local cultures, as well as between local cultures, so that in Southeast Asia it has many roles after the arrival of Islam in various fields, the roles that occur also enter into these various pieces, as in field of education.